Virus-Host Interactions Methods and Protocols - Bailer, Susanne M.; Bailer, Susanne M.; Lieber, Diana.; Lieber, Diana. (Methods in Molecular Biology,, 2013)
Virus-Host Interactions: Methods and Protocols covers various aspects of virological research, such as biochemical approaches, including molecular interactions and regulatory mechanisms on the protein as well as the RNA level with a strong focus on the manifold possibilities to study protein-protein interactions, as well as cell biological and immunological methodologies. Viruses represent a reduced form of life that depends on host cells for propagation. To this end, viruses approach and penetrate cells and usurp cellular machineries for their own benefit. Recent technological improvements have enabled the systematic analysis of the virus-host interplay be it on the genomic, the transcriptomic, or proteomic level. In parallel, bioinformatic tools have emerged in support of the large datasets generated by these high-throughput approaches. Written in the successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and notes on troubleshooting and avoiding known pitfalls. Authoritative and easily accessible, Virus-Host Interactions: Methods and Protocols will prove invaluable to professionals and novices with its well-honed methodologies and protocols.